High-Resolution Visualization of Pseudomonas aeruginosa PAO1 Biofilms by Freeze-Substitution Transmission Electron Microscopy - Hunter, Ryan C. (American Society for Microbiology, 2005)
High-pressure freeze-substitution and transmission electron microscopy have been used for high-resolution imaging of the natural structure of a gram-negative biofilm. Unlike more conventional embedding techniques, this method confirms many of the observations seen by confocal microscopy but with finer structural detail. It further reveals that there is a structural complexity to biofilms at both the cellular and extracellular matrix levels that has not been seen before. Different domains of healthy and lysed cells exist randomly dispersed within a single biofilm as well as different structural organizations of exopolymers. Particulate matter is suspended within this network of fibers and appears to be an integral part of the exopolymeric substance (EPS). O-side chains extending from the outer membrane are integrated into EPS polymers so as to form a continuum. Together, the results support the concept of physical microenvironments within biofilms and show a complexity that was hitherto unknown.